Analysis of Ree-Eyring Fluid Flow With Heat Transfer and Irreversibility Characteristics Over a Stretching Sheet With Variable Thermal Conductivity: A Couple Stress Model - Veeram, Gopinath; Gayatri, Tailam Venkata; Ramana, G. V.; Srikanth, M.; Rao, Darapuneni Purna Chandar; Purushotham, B. (Communications in Mathematics and Applications, 2024)
Ree-Eyring fluids are good models for lubricants. Understanding the flow behavior of these fluids under stretching conditions can help design better lubricants for applications like bearings and gears, especially at varying shear rates. This research delves into the aspects of heat transmission and magnetohydrodynamic movement of the Ree-Eyring fluid across an elastic sheet. The effect of numerous factors on the fluid’s properties, including temperature, is investigated. The equations governing the problem are subjected to transformation and processed with the bvp5c solver. The findings reveal that a stronger magnetic field impedes the fluid flow. Conversely, a higher Ree-Eyring parameter and a higher couple stress parameter promote faster flow rates. The study demonstrates that the Eckert number and heat source parameter contribute to an upsurge in fluid temperature. In contrast, a higher Prandtl number signifies stronger thermal diffusivity, resulting in a lower temperature profile. A higher Brinkman number indicates a more significant role for viscous dissipation, leading to increased entropy generation. The Bejan number, which reflects the relative dominance of heat transmission versus viscous dissipation, decreases with a rise in viscous dissipation. Finally, the study presents mathematical relationships that quantify the impression of these parameters on the friction factor and Nusselt number.